การใช้พืชสมุนไพรผสมอาหารเพื่อเร่งการเจริญเติบโตของปลานิล - แก้วตาปี, วชิรนนท์; วาดวิจิตร์, ประธาน (Community and Social Development Journal, 2011)
บทคัดย่อภาษาไทยไม่สมบูรณ์ The Culture of Tilapia by Additived Feed Herb The culture of reversal tilapia by additived feed herb Pueraria mirifica, Boesenbergia pandurata, Phyllanthus urinaria, Thailentadopsis tenuis and Elephantopus scaber. The different concentrations (0, 20, 40 and 60 g/kg). Result found that weight of tilapia was highest in Elephantopus scaber (161.79 grams), follow by Thailentadopsis tenuis (133.47 grams), Phyllanthus urinaria (127.56 grams) Pueraria mirifica (124.90 grams) and Boesenbergia pandurata (120.44 grams). Tretment with Thailentadopsis tenuis gave a longest length of tilapia. (19.65 centimeter). The highest weight (151.55g) was obtained on treatment with Elephantopus scaber at concentration of 40 gram/feed 1 kg significant difference (P<0.05)